Using Online Interactive Physics-based Video Analysis Exercises to Enhance Learning - Priscilla W. Laws; Robert B. Teese; David P. Jackson; Maxine C. Willis; Kathy Koenig (Karolinum Press, 2017)
As part of our new digital video age, physics students throughout the world can use smart phones, video cameras, computers and tablets to produce and analyze videos of physical phenomena using analysis software such as Logger Pro, Tracker or Coach. For several years, LivePhoto Physics Group members have created short videos of physical phenomena. They have also developed curricular materials that enable students to make predictions and use video analysis software to verify them. In this paper a new LivePhoto Physics project that involves the creation and testing of a series of Interactive Video Vignettes (IVVs) will be described. IVVs are short webbased assignments that take less than ten minutes to complete. Each vignette is designed to present a video of a phenomenon, ask for a student's prediction about it, and then conduct on-line video observations or analyses that allow the user to compare findings with his or her initial prediction. The Vignettes are designed for web delivery as ungraded exercises to supplement textbook reading, or to serve as pre-lecture or pre-laboratory activities that span a number of topics normally introduced in introductory physics courses. A sample Vignette on the topic of Newton's Third Law will be described, and the outcomes of preliminary research on the impact of Vignettes on student motivation, learning and attitudes will be summarized.